Resisting Misogyny and Caste: The Writings of Meena Kandasamy. Issue 1 (June 2016) - Gowrinathan, Nimmi
This article examines the political writing of Meena Kandasamy, online and in print, as it provokes vicious personal attacks which, in themselves, speak to the cultural critique Kandasamy puts forth.